The Effect of Managerial Ownership and Firm Growth on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Ihsan, Muhammad; Rahmadi, Ryand; Aziz, Devin; Gimnastiar, Abim; Jolianis, Jolianis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effect of managerial ownership and firm growth on firm value in the manufacturing sector listed on the Indonesia Stock Exchange (IDX). Managerial ownership is measured based on the percentage of shares owned by the management, while firm growth is measured by the increase in assets and revenue. Firm value is measured using Tobin’s Q as the primary indicator. The data used in this study is secondary data from manufacturing companies listed on the IDX during a selected period, using purposive sampling technique. Data analysis was conducted through multiple linear regression using statistical software. The results show that, simultaneously, managerial ownership and firm growth have a significant impact on firm value. Partially, firm growth has a significantly positive effect on firm value, while managerial ownership shows varying effects depending on the context of the company. These findings indicate that firm growth is an important factor in enhancing firm value, while the role of managerial ownership should be considered along with other factors in investment decision-making. This research provides contributions for investors and management in understanding the factors influencing the firm value of manufacturing companies on the IDX.